2018
DOI: 10.1101/309633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel autotrophic organisms contribute significantly to the internal carbon cycling potential of a boreal lake

Abstract: 36Oxygen stratified lakes are typical for the boreal zone, and also a major source of 37 greenhouse gas emissions in the region. Due to shallow light penetration, restricting 38 the growth of phototrophic organisms, and large allochthonous organic carbon 39 inputs from the catchment area, the lake metabolism is expected to be dominated by 40 heterotrophic organisms. In this study we test this assumption and show that the 41 potential for autotrophic carbon fixation and internal carbon cycling is high 42 throug… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Our analyses show that oxygen impacts metabolic potential, in part by selecting for bacteria and archaea with certain C1 and carbon fixation pathways in different zones of the lake. In particular, the Wood-Ljungdahl and reverse TCA cycle showed strong signals of stratification and were essentially restricted to the lake’s anoxic zone, consistent with findings from another stratified lake [36], although that lake is ∼15 times shallower. Thus, potential for autotrophy via these pathways may vary predictably with geochemical conditions in a scale-independent manner.…”
Section: Discussionsupporting
confidence: 82%
“…Our analyses show that oxygen impacts metabolic potential, in part by selecting for bacteria and archaea with certain C1 and carbon fixation pathways in different zones of the lake. In particular, the Wood-Ljungdahl and reverse TCA cycle showed strong signals of stratification and were essentially restricted to the lake’s anoxic zone, consistent with findings from another stratified lake [36], although that lake is ∼15 times shallower. Thus, potential for autotrophy via these pathways may vary predictably with geochemical conditions in a scale-independent manner.…”
Section: Discussionsupporting
confidence: 82%
“…Many dystrophic lakes are characterized by anoxic bottom waters (hypolimnion) where electron acceptors for respiration are highly depleted. Accordingly, the genomes of hypolimnion microbes show the potential for fermentation and methanogenesis (Peura et al 2015;Peura et al 2018). A high prevalence of archaea also in the surface waters (epilimnion) of these net-heterotrophic, greenhouse-gasemitting systems can be speculated to be the result of anoxic microenvironments (Grossart et al, 2011) and their transitory occurrence in oxygenated waters.…”
Section: Archaeal Contribution and Diversity In Freshwater Lakesmentioning
confidence: 99%
“…6), but with lower percentages of recruited reads compared to strain MWH-Mekk-B1 T , suggesting that P. paneuropaeus possessed lower abundances than P. finlandensis sp. nov. Interestingly, analyses of metagenome samples from Lake Alinen Mustajärvi [52,55], which is located only a few kilometres away from Lake Mekkojärvi and shares with that lake very similar water chemistry, revealed that P. paneuropaeus is more abundant than P. finlandensis sp. nov. in the oxygenated epilimnion of that lake but in the anoxic hypolimnion the abundances were reversed (Fig.…”
Section: Ecology and Biogeographymentioning
confidence: 99%